Pharmacodynamics of Metformin in Pregnant Women With Gestational Diabetes Mellitus and Nonpregnant Women With Type 2 Diabetes Mellitus. (19th November 2019) - Shuster, Diana L.; Shireman, Laura M.; Ma, Xiaosu; Shen, Danny D.; Flood Nichols, Shannon K.; Ahmed, Mahmoud S.; Clark, Shannon; Caritis, Steve; Venkataramanan, Raman; Haas, David M.; Quinney, Sara K.; Haneline, Laura S.; et al.
Abstract: Gestational diabetes mellitus is a condition similar to type 2 diabetes mellitus (T2DM) in that patients are unable to compensate for the degree of insulin resistance, and both conditions are often treated with metformin. The comparative pharmacodynamic response to metformin in these 2 populations has not been studied. This study characterized insulin sensitivity, β‐cell responsivity, and disposition index following a mixed‐meal tolerance test utilizing a minimal model of glucose, insulin, and C‐peptide kinetics before and during treatment with metformin. The study included women with gestational diabetes mellitus (n = 34), T2DM (n = 14), and healthy pregnant women (n = 30). Before treatment, the gestational diabetes mellitus group had significantly higher baseline (45%), dynamic (68%), static (71%), and total β‐cell responsivity (71%) than the T2DM group. Metformin significantly increased insulin sensitivity (51%) as well as disposition index (97%) and decreased mixed‐meal tolerance test peak glucose concentrations (8%) in women with gestational diabetes mellitus after adjustment for gestational age–dependent effects; however, in women with T2DM metformin only significantly affected peak glucose concentrations (22%) and had no significant effect on any other parameters. Metformin had a greater effect on the change in disposition index (Δ disposition index) in women with gestational diabetes mellitus than in those with T2DM ( P = .01). In conclusion, response to metformin in women with gestational diabetes mellitus is significantly different from that in women with T2DM, which is likely related to the differences in disease severity.